Indirect Peer Aggression in Adolescence and Reproductive Behavior - Daniel D. White; Andrew C. Gallup; Gordon G. Gallup (Evolutionary Psychology, 2010)
Evolutionary psychologists have suggested that indirect aggression during adolescence is a strategy to compete with same-sex peer rivals for resources, status, and mating opportunities. We collected survey data on 143 young adults to determine retrospectively, the amount of indirect aggressive behavior they perpetrated and the amount of indirect victimization they experienced in middle school and high school. We also collected information about reproductive opportunities such as age at first sexual intercourse and number of lifetime sex partners to determine whether aggression or victimization could be used to predict measures of reproductive opportunity. We performed a principal components analysis to develop factors from 16 aggression and victimization variables. Results indicate that females who reported indirect aggression toward peers had earlier ages at first sexual intercourse and females who were more victimized in adolescence experienced later ages at first sexual intercourse. We discuss these results in terms of intrasexual competition and evolutionary theory.